(untitled) (Al-Qamar, 2022)
Development is a complex problem that is increasing day by day in developed countries. It has great importance in the last five decades, especially after the Second World War, Economists put forward different ideas on this problem because economic depression and Poverty was a major obstacle to prosperity. Women are the basic unit of society. Men and women are the rare in the universe who built and reform the tribe, family and nations. Women has been working in all Kind of profession in Pakistan. Women participation with men in economic activities which will increase the production and the GDP of country. Neither the nation nor the country can progress on the path of development until women become partners with men. Islam is a religion and a complete code of life which provides complete guidance to human in all aspects of life. Islam takes economic prosperity seriously and considers it as an important part of the overall life of men. Earning a living is not prohibited for a woman. Islam allows women to have a job or business, if necessary, but there are some limitations and regulations that must be followed for the betterment of the society. Quran and Sunna of Holy Prophet ﷺprovide us guide line in this aspect. This Article discusses about that primary men are responsible for earning a living but women can also perform their service for the development of country by adopting the teaching of Islam.